Dakwah and communication programmes in tertiary higher education in Indonesia: a brief survey - Suhaimi (Penerbit Universiti Kebangsaan Malaysia, 2012)
Islamic communication can be defined as the process of delivering message of Islamic teachings in the form of mercy to the world through a variety of media with persuasive methods that will result in the influence of a certain effect. A basic criterion of Islamic communication is persuasive in nature rather than cursive. That means the Islamic dakwah has always sought to influence people to perform any good action in accordance with the religious consciousness via his own will, not by coercion.Coercion is the deprivation of human rights in religion. An utmost criterion in the ?Islamic communication is any delivered message which is based on rational and reasonable to the intellectuality of human beings which invites them to return to their nature.